Whole Exome Sequencing Leading to the Diagnosis of Dysferlinopathy with a Novel Missense Mutation (c.959G>C) - Abhisek Swaika; Nicole J. Boczek; Neha Sood; Kimberly Guthrie; Eric W. Klee; Ankit Agrawal; Elliot L. Dimberg; Sikander Ailawadhi (Case Reports in Genetics, 2016)
Dysferlinopathy is an uncommon, progressive muscular dystrophy that has a wide phenotypic variability and primarily supportive management (Nguyen et al., 2007; Narayanaswami et al., 2014). Amyloid myopathy is a distinct, rare disorder that can present similarly to inflammatory myopathies and requires a high clinical suspicion for early intervention to prolong survival. Amyloid myopathy is typically associated with other systemic manifestations of amyloidosis, but rare cases of isolated amyloid myopathy have been described (Mandl et al., 2000; Hull et al., 2001). Positive Congo red stains on tissue biopsy remain the gold standard for diagnosis (Spuler et al., 1998; Karacostas et al., 2005). A high clinical suspicion and meticulous diagnostic workup that includes novel techniques are necessary for identifying these rare disorders. We report a middle-aged man with progressive leg muscle weakness who was initially treated as having amyloid myopathy but was later diagnosed as having dysferlinopathy by Whole Exome Sequencing (WES) analysis. We also report a novel missense mutation (c.959G>C) to help correlate in any patient with presumed dysferlinopathy and to add to the already known genotype of this disorder.